Sensitive element of multifunctional sensor for measuring temperature, strain and magnetic field induction - Druzhinin, A.A.; Khoverko, Yu.М.; Kutrakov, A.P.; Liakh-Kaguy, N.S.; Yatsukhnenko, S.Yu. (Технология и конструирование в электронной аппаратуре, 2017)
Sensitive element of multifunctional sensor for measuring temperature, strain and magnetic field induction has been developed based on the studies of electrical conductivity and magnetoresistance of silicon and germanium microcrystals in the temperature range 4.2—70 K, strain ±1.5⋅10–3 rel.un. and magnetic fields of 0—14 T. The feature of the sensitive element is the using of the p- and n-type conductivity germanium microcrystals as mechanical and magnetic field sensors, respectively, and the p-type silicon microcrystal — as temperature sensor. That allows providing the compensation of temperature influence on piezoresistance and on sensitivity to the magnetic field.